Aspectos tributários da (re)organização de sociedades de advogados em modelo colaborativo no Brasil - Koch, Dennis Bariani (Universidade do Vale do Rio dos Sinos, 2019)
Faced with the current challenge that plagues many legal professionals, this study aims to shed light on the following problem: What are the relevant tax aspects that law firms must observe in order to reconcile tax and cost efficiency, without restructuring characterizing tax evasion by simulation, form abuse or business group formation? Through a descriptive research method, study of the current legislation and Brazilian administrative and judicial jurisprudence, as well as through sectorial research, the study identifies legally foreseen opportunities in the current legal market for lawyers to rethink current corporate structures, the tax framework or the organizational administrative structure as a way to achieve greater efficiency, competitiveness, reduction of transaction costs, because the Brazilian legal market is one of the largest and most competitive in the world. Before asking whether legal activity in Brazil will be replaced by artificial intelligence, the study is concerned first with pointing out the constitutional limits imposed by tax aspects in the face of opportunities to reduce administrative, operational and tax reframing costs that may justify the true purpose of a restructuring of a law firm. The study aims to answer which tax limits and aspects matter to traditional law firms that, sensitive to the new challenges imposed by the market, want to review their operating, corporate and tax models in search of greater competitiveness and reduction of transaction costs. In the one hand, (re) structuring of law firms that incur abuse of form, lack of business purpose, governing unit acting in shared locations, may characterize tax evasion leading to tax consequences and liabilities. On the other hand, the study points out the possible limits of legitimate restructuring in view of the latest developments in the corporate field brought by Law nº 13.247/16, which amended the Lawyer's Statute (art. 15 of Law nº 8.906/94) to allow sole proprietorships, as well Complementary Law nº 147/2014, which, by amending Complementary Law nº 123/06, brought the possibility of legal activity to adhere to the regime of Simples Nacional and the advent of Law nº 13.874/2019, which “Institutes the Declaration of the Rights of Economic Freedom; establishes free market guarantees; and other measures”. It is concluded that the correct corporate and tax framework can generate large savings in transaction costs for law firms, which certainly demonstrates the serious business purpose, economic freedom, free enterprise, and legitimates structural review through lawful tax planning. In other words, the revision of the corporate model and the option for the most advantageous tax regime requires proving the legality requirement, designated by business purpose, and, given the interpretative fiscal subjectivity, the lack of proof of this legality requirement will bring to the taxpayer relationship possibility of questioning the tax planning, even if it was carried out lawfully.
Keywords: Sociedade de advogados; Reestruturação; Sistema colaborativo; Aspectos tributários; Law firm; Restructuring; Collaborative system; Tax aspects; ACCNPQ::Ciências Sociais Aplicadas::Direito